Implementasi Peraturan Daerah Nomor 23 Tahun 2014 Tentang Retribusi Izin Tempat Penjualan Minuman Beralkohol Kota Palangka Raya - Fitriani Fitriani; Wahyu Rizanu Arifandi (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2020)
This study aims to determine how the Department of Industry and Trade of Palangkaraya City in implementing Regional Regulation No. 23 of 2014 to the Palangkaraya Alcoholic Beverage Seller. The method used is qualitative. The researcher wants to describe the Implementation of Regional Regulation No. 23 of 2014 from the Department of Industry and Trade of Palangka Raya City to the Seller of Alcoholic Beverages. The author uses 4 (four) indicators of policy implementation namely Information, Policy Content, Community Support and Potential Distribution. The data source consists of primary data, namely the results of interviews with Dinas Perindustrian dan Perdagangan, Alcoholic Beverage Sellers and the people of Palangka Raya City, while secondary data sources are in the form of official Regional Regulation Number 23 of 2014. the results of research on the Implementation of Regional Regulation No. 23 of 2014 are still not optimal due to the difficulty of some Alcoholic Beverage Sellers to be present on time to attend socialization activities and the difficulty of Alcoholic Beverage Sellers in requesting identity cards to teenage buyers. For this reason, the researcher recommends 1) giving a warning to the Alcoholic Beverage Sellers who are late in participating in the Socialization activities and 2) reaffirming the provision of information regarding the Regulations on the prohibition of selling alcoholic drinks to students or under 17 years of age.